The Landscapes of Eco-Noir - Mrozewicz Anna Estera (Nordicom Review)
This article examines the Norwegian climate fiction television series Okkupert [Occupied] (2015–), focusing on the ways in which it reveals the complicity of Nordic subjects in an ecological dystopia. I argue that in illuminating this complicity, the series reimagines the Norwegian national self-conception rooted in a discourse of Norway's exceptionalist relation to nature. I show how Norway's green (self-)image is expressed through what I call “white ecology” – an aesthetics of whiteness encoded in neoromantic mountainous winter landscapes widely associated with the North, but also in the figure of the Norwegian white male polar explorer. I argue in this article that Occupied challenges this white-ecological masculine discourse through “dark ecology” (Morton, 2007), embodied by Russia and expressed by the avoidance of spectacular landscape aesthetics as well as by the strategy of “enmeshment”, facilitated by the medium of televisual long-form storytelling and the eco-noir aesthetics.